Assessment of termal performance in metallic container kiosks in Brasília (Research, Society and Development, 2022)
The architecture design must meet both energy efficiency and user comfort conditions. NBR 15575-1 (ABNT, 2013) states that the thermal performance of the building must be assessed under two conditions: summer performance and winter performance. The analysis criteria is based on maximum and minimum temperature values of the extended-stay environments. In order to attempt the criteria proposed by the regulation, computer simulations were used to create different construction scenarios, including container steel sheets for supposed kiosks in Brasília city. It was observed in the computational simulations that the kiosks, because they are made of steel, suffer big influence of the external temperatures and of the insolation, being necessary the use of other strategies to improve the thermal performance. Knowing that, it is noticed that the use of thermal insulation is indispensable in Brasília bioclimatic zone, where, according to normative recommendations, temperature and relative humidity are not ideal. Among the scenarios proposed in the simulation, the containers that showed better performance were the ones that used an additional coverage and the ones that used drywall plasterboard with a rock wool insulation to obtain cooler temperatures in summer and more pleasant internal temperatures to the occupants in winter.